Occupational Safety and Health (OSH) Risk Management Analysis of Hazardous Waste Treatment Using the HIRARC and Bowtie Analysis Methods - Prisilia, Harliwanti; Purnomo, Dimas Aji; Rofiq, Ainur (2477 - 6165, 2025)
The management of hazardous medical waste is an important aspect in maintaining occupational safety and the environment in healthcare facilities. Medical waste collection activities have high potential hazards, such as the risk of needle stick injuries, chemical exposure, and biological contamination. This study aims to analyze the potential hazards and risks in the process of collecting hazardous medical waste using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) and Bowtie Analysis methods. The HIRARC method is used to identify hazards, assess risk levels, and determine appropriate control measures, while the Bowtie method is used to map the relationship between causes, top events, consequences, and controls. The results of the analysis show that hazards with high risk levels originate from direct contact with sharp objects and infectious materials. Recommended control measures include the use of complete Personal Protective Equipment (PPE), routine training on waste handling, and the implementation of strict standard operating procedures. The integration of the HIRARC and Bowtie methods proved effective in providing a comprehensive overview of potential hazards and risk control strategies in the collection of hazardous medical waste, thus improving work safety and preventing environmental pollution.